The distribution of household savings in Germany - Jochen Späth; Kai Daniel Schmid (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2016)
Savings are, apart from inheritances and transfers, the corner stone for the accumulation of wealth. Against the background of rising economic inequality in industrialized countries and the ongoing assessment of its root causes, analyses of the distribution of savings along the income and wealth distribution are of high interest for the question on whether mutual stimulation between income flows and wealth stocks contributes to rising inequality. We analyze the extent of the concentration of household savings in Germany by estimating saving amounts, saving rates and shares in aggregate savings for different classes of household income and household wealth in Germany. Our calculations are based on the Sample Survey of Household Income and Expenditure (in German: Einkommens- und Verbrauchsstichprobe - EVS), a large sample containing more than 40,000 households in Germany. We show that the concentration of savings in Germany is substantial, as in 2013 the top income decile's share in aggregate savings amounts to about 60 percent, whereas the lower half of the income distribution actually does not save at all. Conditional on the distribution of wealth the concentration of savings is somewhat less pronounced, but still apparent. Over the years 2003 till 2013 we find an increase of the concentration of household savings across the income and wealth distribution. Finally, based on a set of assumptions, we look beyond the top income threshold underlying the EVS dataset (18,000 euros of monthly net household income) in order to estimate bias-corrected saving rates for the top income groups which are considerably higher than those that can be calculated with our data set alone. Using these corrected saving rates as input parameters for a macro simulation of the distribution of household incomes and savings we find that the aggregate saving rate increases by two to three percentage points compared to the estimate based on EVS data alone. Also, the top decile and percentile groups' shares in aggregate savings are substantially higher compared to the estimates solely based on EVS data. – – Die Studie schätzt Sparvolumen, Sparquote und Anteile am aggregierten Sparvolumen für verschiedene Klassen von Haushaltsnettoeinkommen und Haushaltsnettovermögen in Deutschland. Es werden Daten der Einkommens- und Verbrauchsstichprobe (EVS) verwendet, welche über 40.000 Haushalte in Deutschland erfasst. Unsere Berechnungen basieren auf der aktuellsten Stichprobe für das Jahr 2013. Die Eignung und Qualität der Daten ist sehr hoch, da u.a. die Haushaltsersparnisse aus einer detaillierten Auflistung aller Einnahmen und Ausgaben abgeleitet werden und eigenständig erhoben werden. Nachteile von Umfragen, wie Erinnerungslücken oder Framing können so umgangen werden.Unsere Untersuchung zeigt, dass die Haushaltsersparnis in Deutschland entlang der Einkommens- und Vermögensverteilung sehr stark konzentriert ist. Während sich die untere Hälfte der Einkommensverteilung im Jahr 2013 im Durchschnitt um ungefähr 300 Euro verschuldete, betrug die jährliche Ersparnis von Haushalten des obersten Einkommensperzentils durchschnittlich ungefähr 60.000 Euro. Entlang der Vermögensverteilung sind die Ersparnisse in Deutschland weniger konzentriert. Die untere Hälfte der Vermögensverteilung sparte 2013 im Durchschnitt 1.500 Euro, das oberste Vermögensperzentil dagegen durchschnittlich etwa 24.000 Euro.Auch die Sparquoten steigen mit dem Einkommen und dem Vermögen. Die untere Hälfte der Einkommensverteilung verschuldete sich 2013 im Durchschnitt um 1,6 Prozent ihres Einkommens, während das oberste Perzentil durchschnittlich 35 Prozent sparte. Entlang der Vermögensverteilung sparte die untere Hälfte etwa 6 Prozent im Jahr 2013. Das Top-Vermögensperzentil erreichte eine Sparquote von etwas mehr als 25 Prozent.Am deutlichsten sichtbar wird die hohe Konzentration der Haushaltsersparnis beim Blick auf die Anteile der einzelnen Einkommens- und Vermögensklassen an der Gesamtersparnis. Im Jahr 2013 besaß die höchste Dezilgruppe der Einkommensverteilung knapp 60 Prozent aller Ersparnisse, während die untere Hälfte in Summe nicht sparte. Auf die untere Hälfte der Vermögensverteilung entfallen etwa 18 Prozent, auf das Top-Vermögensdezil knapp 30 Prozent der Ersparnis. Über die Zeit zeigt sich ein relativ stabiler Anstieg der Konzentration der Ersparnis entlang der Verteilung der Haushaltseinkommen und -vermögen.Wir veranschaulichen zudem, dass wir aufgrund der EVS-Einkommensobergrenze von 18.000 Euro monatlichem Haushaltsnettoeinkommen die Sparquote und die Konzentration der Haushaltsersparnis unterzeichnen. So wird beispielsweise der Anteil des Top-Einkommensdezils am gesamten Sparvolumen ohne Korrektur um ungefähr 10 Prozentpunkte unterschätzt.
urn:nbn:de:101:1-201611114206
Keywords: D14; E21; 330; Household Savings; Saving Rate; EVS; Administrative Data; Inequality; Endogenous Accumulation